(untitled) (Research, Society and Development, 2024)
Research on 24-hour behavior in elderly individuals with non-communicable chronic diseases (NCDs) is still in its early stages and presents gaps. The main limitations include population heterogeneity, inconsistent definitions and measures, inadequate study selection, methodological limitations, inadequate synthesis of results, and inconclusiveness of findings. Considering these limitations, there is an urgent need for more research to better understand 24-hour behavior in this population and develop effective interventions to promote health and well-being. Factors such as health conditions, level of physical activity, and lifestyle should be considered, as well as appropriate definition and measurement of 24-hour behavior. Comprehensive understanding of 24-hour behavior in this population will allow for the development of personalized and effective interventions to improve the health and quality of life of elderly individuals with NCDs. The present study aims to develop and describe a protocol for systematic review in the area of 24-hour behavior in elderly individuals with non-communicable chronic disease, and its respective operational aspects. The registration of this protocol was done in PROSPERO, using the electronic databases PubMed, Web of Science, and Scopus to identify articles. The PRISMA flowchart was used to synthesize and structure the results according to the inclusion/exclusion of studies.